Torasemide – loop diuretic with specific effects - V. M. Gorbunov; R. G. Oganov (Кардиоваскулярная терапия и профилактика)
A loop diuretic torasemide is characterized by high bioavailability and prolonged action, explaining some beneficial pharmacodynamic features of the medication. Demonstrating a clear antihypertensive effect, torasemide can be used as monotherapy or combined with other antihypertensives. Torasemide benefits, comparing to furosemide, in chronic heart failure treatment have been confirmed in numerous large-scale studies. Its pharmacokynetics remains virtually unchanged in patients with chronic liver or renal failure. Adverse effects are similar to those in other diuretics, by both quality and quantity. Therefore, torasemide can be used more widely in modern clinical practice.